Analisis Data Sentimen Kepuasan Pengguna E-Wallet Menggunakan Metode K-Nearest Neighbor - Saputra, Muhardi; Hafiz, M.; Situmorang, Indah Permata Sari; Lumbantobing, Gilbert Jonatan; Matullessya, Steven Michael (STIKOM Tunas Bangsa Pematangsiantar, 2024)
E-Wallet or commonly known as a digital wallet, is an electronic payment service that allows users to conduct financial transactions without physical cards or cash. This research aims to obtain the percentage results of user satisfaction with E-Wallet platform services such as Dana, Ovo, Gopay, and Shopeepay among university students in the city of Medan. This research is using a quantitative approach, where data collection was carried out utilizing Google Forms as the questionnaire medium with 8 assessment indicators for the application with data obtained from 400 respondents. Data processing is using the Machine Learning algorithm K-Nearest Neighbor (K-NN), which is a classification algorithm, with an 80% training data and 20% test data split. The results of this study show that the satisfaction percentage for Dana reached 84%, Ovo has the highest satisfaction percentage at 93%, Gopay at 90%, and Shopeepay at 88%.